Heat‐Triggered Ferri‐to‐Paramagnetic Transition Accelerates Redox Couple‐Mediated Electrocatalytic Water Oxidation. (20th May 2022) - Liu, Duanduan; Lu, Mengfei; Liu, Depei; Yan, Shicheng; Zhou, Wei; Zhang, Lunyong; Zou, Zhigang
Abstract: Redox couple oxidation as an initial step of water oxidation may be key for high electricity consumption in the electrochemical oxygen evolution reaction (OER). Here, a heat‐induced magnetic transition strategy is reported to speed up the oxidation kinetics of redox couples. The activation energy of Ni 2+ /Ni 3+ redox couple oxidation is sharply decreased by heating the Ni0.67 Fe0.33 O x H y catalyst above a Curie temperature ( T c ) of 70 °C. In such a strategy, heat instead of electricity drives the spin flipping of Ni 2+ /Ni 3+ oxidation through heat‐sensitive ferri‐to‐paramagnetic spin state changes. As a result of magnetic transition‐assisted efficient heat‐electricity coupling, Ni0.67 Fe0.33 O x H y exhibits the lowest OER overpotential of 221 mV at 100 mA cm −2 at 90 °C in alkaline electrolytes, outperforming the benchmark IrO2 catalyst. The findings provide new insights into the design of efficient heat–electricity complementary OER devices. Abstract : A heat‐induced magnetic transition strategy is proposed to accelerate the oxidation kinetics of catalytic redox couple, a vital initial oxygen evolution reaction step, aiming to achieve ferri‐to‐paramagnetic spin flipping by heat instead of electricity. This strategy provides a solid physical basis for heat‐electricity coupling and unlocks the great potential of heat–electricity complementary water electrolysis by utilizing a low‐grade thermal field.